Optimizing Cyber Media as an Islamic Education and Da'wah Tool: A Case Study of Majelis Ulama Indonesia (MUI) DKI Jakarta - Ahmad Irfan; Ahamd Yunus; Ayuhan Ayuhan; Siti Nuri Nurhaidah (Jurnal Studi Pendidikan Agama Islam, 2026)
In the digital age, cyber media has become a strategic platform for the dissemination of information, knowledge, and religious values. This study examines the role of the Indonesian Ulema Council (MUI) of DKI Jakarta in optimizing cyber media as a tool for Islamic preaching and education. This study aims to examine the optimization of cyber media as an instrument for Islamic da’wah and education by the Indonesian Ulema Council (MUI) of DKI Jakarta. The research method employs a descriptive-analytical qualitative approach, with the research location at the MUI DKI Jakarta secretariat office and its digital ecosystem, encompassing the official website, social media accounts, and online content channels. The results indicate that the MUI of DKI Jakarta has implemented a digital transformation encompassing three main dimensions: digital infrastructure development, multi-platform content management, and human resource capacity building. The utilization of social media platforms and the official website has proven to expand the reach of da’wah and enhance access to Islamic education for urban communities. An editorial mechanism based on verification by religious scholars is implemented to ensure the accuracy of religious information. Nevertheless, this study identified several challenges, including a digital skills gap, fragmentation of religious authority, and reliance on third-party platforms. Therefore, the Jakarta MUI needs to strengthen its collaborative ecosystem and diversify the digital infrastructure of religious institutions.